Oromandibular parafunction in chronic graft‐versus‐host disease: novel association and treatment approach. Issue 11 (18th November 2021) - Joshi, Purwa; Kiers, Lynette; Evans, Andrew; Ritchie, David; Szer, Jeff; Cruse, Belinda
Abstract: Chronic graft‐versus‐host disease (cGVHD) complicating allogeneic haemopoietic stem cell transplantation rarely involves the nervous system; oromandibular parafunction has not been previously reported. We describe five patients with cGVHD, presenting with bruxism, limitation of mouth opening, jaw locking, pain and masseter hypertrophy. Pathophysiological mechanisms are discussed. Targeted botulinum toxin injections were an effective treatment with minimal side‐effects.